Prevalence of tomato potato psyllid (Bactericera cockerelli Sulc) on red capsicum fruit in choice and nochoice tests - Jamieson, L.E.; Page-Weir, N.E.M.; Griffin, M.J.; Redpath, S.P.; Chhagan, A. (New Zealand Plant Protection, 2016)
Tomato potato psyllid (TPP; Bactericera cockerelli) was first recorded in New Zealand in 2006 Exports to Australia must be fumigated with methyl bromide (MB) to comply with New Zealands phytosanitary export certification requirements Fumigation reduces the quality of the capsicums In tests using high densities of TPP adults TPP laid eggs mainly on the top of the calyx and the stem and some on the body of the fruit although far fewer eggs than were laid on tomato or capsicum leaves Given the choice between capsicum fruit body stem and calyx or capsicum leaves 992995 of eggs were laid on leaves Nymphs that hatched from the few eggs laid on the calyx and stem did not survive indicating that capsicum fruit are a poor host for TPP No eggs were laid beneath the capsicum calyx Some exported capsicums are washed using high pressure washing equipment which might dislodge TPP eggs The very low incidence and survival of TPP on capsicum fruit could result in this fruit already meeting or exceeding the phytosanitary requirements of the importing country